The Occurrence of Streptococcus Mutans and Oral Health Condition in Pregnant Women - H. Hecová; V. Merglová; J. Stehlíková; P. Chaloupka (Czech Dental Chamber, 2012)
Introduction: Occurrence of cariogenic microorganisms in the oral cavity is considered as a major etiologic factor causing dental caries. Cariogenic SM streptococcal exposure is significantly affected both by carbohydrates in diet and saliva buffer capacity. Aims: The aim of this study was to investigate the dental status of pregnant women, to determine the saliva buffer capacity, and to identify the occurrence of Streptococcus mutans (SM) quantity in saliva and plaque. The frequency of carbohydrate intake in between meals among pregnant women was taken as a base for the risk determination of new carious lesions. Materials and methods: The study included 61 women with a physiological pregnancy (group F) and 81 women with a risk pregnancy (group R). The age range of women in both groups was 21 to 40 years. Results: The study results showed following: the risk values of SM in saliva were detected in 65.5% of women with a physiological course of pregnancy and in 70.3% of women with a risk course of pregnancy. The risk values of SM in the plaque were found in 82% of women in group F and in 85.2% of women in group R. The low saliva buffer capacity was found in 51 pregnant women. The middle saliva buffer capacity was detected in 51 pregnant women.The average value of the DMF amounted to 11.3 and 12.8 in women of F and R groups respectively.Untreated caries occurred in 94 pregnant women (52.5% in physiologic pregnancy and 76.5% in risk pregnancy).Dental caries destruction resulted in an extraction in 4 women (group F) and 10 women (group R). High risk of new caries lesions were found more frequently in the women with risk pregnancy (71.6). The differences in salivary and plaque levels of SM and saliva buffer capacity between groups of women with physiological and risk course of pregnancy were not statistically significant. Nevertheless the need of dental treatment in women at risk pregnancy was statistically significantly higher than in women at physiological pregnancy (P = 0.0027). Conclusion: The study has emphasized the need of increased attention during preventive dental appointments particularly in women with a risk course of pregnancy.